39.0k views
3 votes
What is the solution to 0.4(12-3x)=0.3(12x-16)

1 Answer

8 votes

Step 1: Simplify both sides of the equation.

0.4(12−3x)=0.3(12x−16)

(0.4)(12)+(0.4)(−3x)=(0.3)(12x)+(0.3)(−16)(Distribute)

4.8+−1.2x=3.6x+−4.8

−1.2x+4.8=3.6x−4.8

Step 2: Subtract 3.6x from both sides.

−1.2x+4.8−3.6x=3.6x−4.8−3.6x

−4.8x+4.8=−4.8

Step 3: Subtract 4.8 from both sides.

−4.8x+4.8−4.8=−4.8−4.8

−4.8x=−9.6

Step 4: Divide both sides by -4.8.

−4.8x /−4.8 = −9.6 /−4.8

x = 2

User SabareeshSS
by
5.7k points